THE AGILE APPROACH IN INDUSTRIAL AND SOFTWARE ENGINEERING PROJECT MANAGEMENT - Jovanovic, Milos; Lalić, Bojan; Mas, Antonia; Mesquida, Antoni-LIius (Journal of Applied Engineering Science, 2015)
The paper presents the agile approach in industrial engineering and discusses similar ways of agile development in different disciplines. Societal changes and technological innovation brought significant changes in the market, leading to highly demanding users and frequent changes in product design. Agile is implemented in different disciplines as a response to current changes in the market. Industry 4.0 as part of “High-Tech Strategy 2020 for Germany” involves agile principles and brings latest technological trends in production process. Agile framework was firstly used in manufacturing but along with that it started to develop as a lightweight framework in software development. Agile is interdisciplinary and brings flexibility to organization. For successful implementation of agile principles, experiences and recommendations from all the industries should be used.
Keywords: Project management; Agile software development; Industry 4.0; Agile manufacturing